Characterization of a novel N-acylhomoserine lactonase, AidP, from Antarctic Planococcus sp. - See-Too, Wah Seng; Convey, Peter; Pearce, David Anthony; Chan, Kok Gan (BMC, 2018)
BACKGROUND: N-acylhomoserine lactones (AHLs) are well-studied signalling molecules produced by some Gram-negative Proteobacteria for bacterial cell-to-cell communication or quorum sensing. We have previously demonstrated the degradation of AHLs by an Antarctic bacterium, Planococcus versutus L10.15T, at low temperature through the production of an AHL lactonase. In this study, we cloned the AHL lactonase gene and characterized the purified novel enzyme. RESULTS: Rapid resolution liquid chromatography analysis indicated that purified AidP possesses high AHL-degrading activity on unsubstituted, and 3-oxo substituted homoserine lactones. Liquid chromatography-mass spectrometry analysis confirmed that AidP functions as an AHL lactonase that hydrolyzes the ester bond of the homoserine lactone ring of AHLs. Multiple sequence alignment analysis and phylogenetic analysis suggested that the aidP gene encodes a novel AHL lactonase enzyme. The amino acid composition analysis of aidP and the homologous genes suggested that it might be a cold-adapted enzyme, however, the optimum temperature is 28 °C, even though the thermal stability is low (reduced drastically above 32 °C). Branch-site analysis of several aidP genes of Planococcus sp. branch on the phylogenetic trees also showed evidence of episodic positive selection of the gene in cold environments. Furthermore, we demonstrated the effects of covalent and ionic bonding, showing that Zn2+ is important for activity of AidP in vivo. The pectinolytic inhibition assay confirmed that this enzyme attenuated the pathogenicity of the plant pathogen Pectobacterium carotovorum in Chinese cabbage. CONCLUSION: We demonstrated that AidP is effective in attenuating the pathogenicity of P. carotovorum, a plant pathogen that causes soft-rot disease. This anti-quorum sensing agent is an enzyme with low thermal stability that degrades the bacterial signalling molecules (AHLs) that are produced by many pathogens. Since the enzyme is most active below human body temperature (below 28 °C), and lose its activity drastically above 32 °C, the results of a pectinolytic inhibition assay using Chinese cabbage indicated the potential of this anti-quorum sensing agent to be safely applied in the field trials.